Association of Polymorphisms in NHEJ Pathway Genes with HIV-1 Infection and AIDS Progression in a Northern Chinese MSM Population. (19th October 2022) - Zhang, Xuelong; Wang, Xi; Mo, Han; Hu, Yuanting; Yang, Yi; Yang, Xun; Wu, Jiawei; Liu, Bangquan; Xu, Lidan; Sun, Haiming; Jia, Xueyuan; Wang, Ping; et al.
Abstract : Background and Aims . Men who have sex with men (MSM) are at high risk of HIV infection. The nonhomologous end joining (NHEJ) pathway is the main way of double-stranded DNA break (DSB) repair in the higher eukaryotes and can repair the DSB timely at any time in cell cycle. It is also indicated that the NHEJ pathway is associated with HIV-1 infection since the DSB in host genome DNA occurs in the process of HIV-1 integration. The aim of the present investigation was to evaluate associations of single-nucleotide polymorphisms (SNPs) in NHEJ pathway genes with susceptibility to HIV-1 infection and AIDS progression among MSM residing in northern China. Methods . A total of 481 HIV-1 seropositive men and 493 HIV-1 seronegative men were included in this case-control study. Genotyping of 22 SNPs in NHEJ pathway genes was performed using the SNPscan™ Kit. Results . Positive associations were observed between XRCC6 rs132770 and XRCC4 rs1056503 genotypes and the susceptibility to HIV-1 infection. In gene-gene interaction analysis, significant SNP-SNP interactions of XRCC6 and XRCC4 genetic variations were found to play a potential role in the risk of HIV-1 infection. In stratified analysis, XRCC5 rs16855458 was significantly associated with CD4+ T cell counts in AIDS patients, whereas LIG4 rs1805388 was linked to the clinical phases of AIDS patients. Conclusions . NHEJ gene polymorphisms can be considered to be risk factors of HIV-1 infection and AIDS progression in the northern Chinese MSM population.